Cu2O@PNIPAM core–shell microgels as novel inkjet materials for the preparation of CuO hollow porous nanocubes gas sensing layers. Issue 27 (27th June 2018) - Jia, He; Gao, Haitao; Mei, Shilin; Kneer, Janosch; Lin, Xianzhong; Ran, Qidi; Wang, Fuxian; Palzer, Stefan; Lu, Yan
Abstract : CuO porous hollow sensing layers can be easily formed by heating Cu2 O@PNIPAM printed layers, which show faster response to relevant trace NO2 gases than sensors produced from bare Cu2 O nanocubes. Abstract : There has been long-standing interest in developing metal oxide-based sensors with high sensitivity, selectivity, fast response and low material consumption. Here we report for the first time the utilization of Cu2 O@PNIPAM core–shell microgels with a nanocube-shaped core structure for construction of novel CuO gas sensing layers. The hybrid microgels show significant improvement in colloidal stability as compared to native Cu2 O nanocubes. Consequently, a homogeneous thin film of Cu2 O@PNIPAM nanoparticles can be engineered in a quite low solid content (1.5 wt%) by inkjet printing of the dispersion at an optimized viscosity and surface tension. Most importantly, thermal treatment of the Cu2 O@PNIPAM microgels forms porous CuO nanocubes, which show much faster response to relevant trace NO2 gases than sensors produced from bare Cu2 O nanocubes. This outcome is due to the fact that the PNIPAM shell can successfully hinder the aggregation of CuO nanoparticles during pyrolysis, which enables full utilization of the sensor layers and better access of the gas to active sites. These results point out great potential of such an innovative system as gas sensors with low cost, fast response and high sensitivity.